ENSAYO DE UNA BACTERINA PARA LA PREVENCION DE LA BRUCELOSIS EN ANIMALES DE LABORATORIO - VALDES ORNELAS, OSCAR; GARCIA, A (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
To stain the precollagenous fibers the double Ag impregnation technic of Rio-Hortega is modified by using Ag carbonate in pyridine at 40-45[degree]C followed by washing, reduction in formalin, washing, and treatment with 1 500 Au chloride increasing from
AN ESC NAC CIENC BIOL
Keywords: ENSAYO, BACTERINA, PREVENCION, BRUCELOSIS, ANIMALES DE LABORATORIO; CIENCIAS DE LA VIDA; MICROBIOLOGIA; BACTERIOLOGIA